Effectiveness of Using Video Materials for Teaching English Stories - Kafle, Durga (Kanakai Journal, 2022)
This study attempts to find out whether the use of video materials in teaching English stories is more effective than teaching via text reading and the lecture method. Quasi-experimental research was adopted for the study. Fifty students of Grade seven from an institutional school were taken as the source of data and the sampling procedure was systematic. The fifty students were divided into two groups of each twenty-five, controlled and experiment, and two tests were taken. First, a pre-test before using the Video materials as teaching, and second, a post-test after the researcher used video materials to teach the experiment group whereas she used the same lecture method to teach the controlled group. After using the video material as a new technique, the interest of the students in learning English stories was found to have increased.